1989
DOI: 10.1021/j100347a006
|View full text |Cite
|
Sign up to set email alerts
|

Observation of high-energy backward scattered ions in a beam study of threshold energy collision-induced dissociation: dynamics of a long-lived excited state of the acetone molecular ion

Abstract: Collision-induced dissociation of acetone molecular ions with helium as a target gas has been studied at 0.65and 0.45-eV center-of-mass collision energies. Scattering contour maps show that fragment ions, CH3CO+, are predominantly backward scattered with intensity maxima lying well outside the elastic scattering circle. This can occur only by the conversion of internal energy into translational energy, demonstrating the presence of long-lived (r > 30 µ$) excited states of the acetone molecular ion. From the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…The molecular beam experiments which directly measure the energy transfer in a single collision and the kinetic energy dependence of energy transfer support the concept that CID for small polyatomic molecular ions is best described as a curve‐crossing mechanism which mainly involves impulsive collisions 29, 39. In many ways this is conceptually similar to endothermic charge‐transfer processes.…”
Section: Energy Transfermentioning
confidence: 86%
See 1 more Smart Citation
“…The molecular beam experiments which directly measure the energy transfer in a single collision and the kinetic energy dependence of energy transfer support the concept that CID for small polyatomic molecular ions is best described as a curve‐crossing mechanism which mainly involves impulsive collisions 29, 39. In many ways this is conceptually similar to endothermic charge‐transfer processes.…”
Section: Energy Transfermentioning
confidence: 86%
“…Energy exchange is maximized when the collision time is matched to the level width of the transition and declines essentially exponentially at higher velocity. As demonstrated from several studies, for CID processes the photoelectron spectrum frequently provides clues to the existence of isolated states which result in deviation from the simplest formalism of energy transfer 29, 39…”
Section: Energy Transfermentioning
confidence: 99%
“…gradually shifts the average energy deposition to higher values, saturating at about 6 eV average energy deposition); 2. ions initially in the A state are excited to higher vibronic states (and the dissociation also occurs on the electronically excited surfaces) or, at very low collision energies, are deexcited to the X state with sufficient vibrational excitation to dissociate on the ground-state hypersurface {that is, at very low collision energies (Eon < 2 eV), collision with rare gas atoms triggers the release of stored electronic energy (the adiabatic X ..... A difference; 2.2 eV) into recoil kinetic energy of the acetone ion which then rapidly dissociates into MeCO+ and Me' on the ground-state potential surface because vibrational energy in the acetone ion exceeds its dissociation limit on that surface [33,34]}.…”
Section: Discussionmentioning
confidence: 99%
“…Qian et al [34,41] recently reviewed the available information about the unimolecular dissociation and CAD of the acetone, methyl nitrite, and nitromethane cations. They indicated that several of these studies had concluded that the dissociation of the nitromethane [42,43] and methyl nitrite [43,44] cations (to NO+, MeO+, and Me+) and acetone cation (to MeCO+ [17,23,25,27,[30][31][32][33][34] and Me+ (29]) cannot be described by QET. J Am Sue Mass Spectrum 1992,3,427-444…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation